COMUNICAÇÃO PARA OS PEQUENOS NEGÓCIOS: PROPOSTA DE MODELO DE APLICAÇÃO PRÁTICA PARA POSICIONAMENTO EM MÍDIAS E REDES SOCIAIS DIGITAIS - Colnago, Camila Krohling (2014)
The limited financial means and limited administrative structure are in part the shortcomings for the small start-up business in quickly achieving results. To overcome these shortcomings, small businesses must develop a communication strategy to reach the greatest number of customers and one of the vehicles to achieve the goal of strategically positioning the business is the use of the internet in cost effective manner. The objective of this thesis is to address the importance of developing an efficient and effective communication structure specifically as it applies to small emerging businesses with limited resources using the social networks and digital media and an in depth analysis of the elements to be employed to achieve the business objectives of individual business owner operators, micro enterprises and small businesses. As a preface, included are bibliographic studies in support of the research for the understanding of the infrastructures of small business and communication structures. These studies laid the foundation to the proposed model The Practical Guide for use Social Networks and Digital Media for Strategic Positioning for Small Businesses and the research was concluded with a qualitative analysis of: a) the use of the proposed model by three different small businesses over a period of three months; and b) the evaluation of the proposed model. The results of this research suggest that despite positive contributions of the Practical Guide for the use Social Networks and Digital Media for Strategic Positioning for Small Businesses in improving the strategic positioning for the small business, in general communications alone will not fall short because of the internal limitations small business structures.